Information Technology Services and School Libraries: A Continuum of Social Justice - Dadlani, Punit PT; Todd, Ross (Qualitative and Quantitative Methods in Libraries, 2017)
This brief paper first develops a social justice typology that maps out conceptions of social justice and their relationship to library services. Based on this typology, it presents research findings that seek to understand what social justice principles facilitate the provision of information technology service in school libraries. This paper is based on data from focus groups of seven exemplary high school libraries in the state of New Jersey. Using a social justice framework, it was found that no single social justice principle guided specific actions of the school libraries studied; instead a process of moving between different principles of egalitarianism and utilitarianism based on resource availability was used by teachers and school librarians in providing information technology service to their respective schools. This research presents a qualitative methodology for studying social justice principles that addresses the sustainability of school libraries and their ongoing transformation and development as community information technology hubs and learning centers.